2016
DOI: 10.13080/z-a.2016.103.046
|View full text |Cite
|
Sign up to set email alerts
|

Microdochium nivale and M. majus as causative agents of seedling blight in spring cereals

Abstract: Seedling blight, mostly caused by Fusarium spp. and Bipolaris sorokiniana, is a common disease in spring cereals. This research confirmed the presence of Microdochium fungi in a complex of seedling blight causative agents. Pathogens Microdochium nivale and M. majus in the seed and in stem base of seedlings of spring barley, spring wheat, spring triticale and spring oats were identified and quantified using a quantitative real-time polymerase chain reaction (qPCR) in 2013-2015. Both species were detected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(32 reference statements)
3
9
1
Order By: Relevance
“…It has been reported that these fungi have occurred in >90% of grain samples in Denmark over the years [23]. Previously, only M. nivale was recognized as a wheat pathogen, but the latest findings have also revealed the pathogenicity of M. majus [24]. The occurrence of both fungi was also high in our investigation, reaching on average 40% in the 5 years.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that these fungi have occurred in >90% of grain samples in Denmark over the years [23]. Previously, only M. nivale was recognized as a wheat pathogen, but the latest findings have also revealed the pathogenicity of M. majus [24]. The occurrence of both fungi was also high in our investigation, reaching on average 40% in the 5 years.…”
Section: Discussionsupporting
confidence: 63%
“…Fludioxonil (Glynn et al 2007;Glynn et al 2008) and sedaxane (Zeun et al 2013) have been previously shown to effectively control Microdochium spp. in vitro and in field (Jonavičienė et al 2016). Furthermore, in this study, sedaxane as part of a mixture with fludioxonil, under high disease pressure significantly increased plant counts at GS 39 by 29% compared to the untreated.…”
Section: Matthew Brown Plant Diseasesupporting
confidence: 50%
“…Information about the diseases, such as pink snow mold, grass decay, leaf spots, and head blight, caused by Microdochium fungi has been published previously [2][3][4][5][6][7][8]. Microdochium fungi were first identified in 1849 by Fries as Lanosa nivalis, which was later (1886) reclassified and placed in the genus Fusarium as F. nivale Ces.…”
Section: Introductionmentioning
confidence: 99%